Impacto de la roya en el Crecimiento Económico de la provincia de San Martín 2009 – 2013 - Caballero Ramírez, Shirley Banessa (2015)
San Martin Region has 584 health committees covering more than 16 thousand coffee farmers, of which 98% received agricultural inputs to control stripe rust, besides being trained in issues of agronomic crop management through pruning, fertilizing or plant Fertilizers and soil improvement, in order to deliver a strong plant for better and higher productivity Coffee rust is considered one of the most catastrophic diseases throughout history plants. It is within the seven plagues and / or plant disease that has left major losses in the last 100 years. It is the main phytosanitary problem of high impact for coffee production. Losses in Latin America is estimated at 30% of the crops. The research aims to determine the impact of rust on economic growth of the Province of St. Martin in the period 2009 - 2013, through signing techniques, information gathering, which was used for the development of this research . It is experimental: since the study variables are manipulated; Design Pre - experimental: because the variable is measured in two time periods other than this way to solve the issues raised, also for the analysis and interpretation of data programs Excel, SPSS and Word is used by tables and graphs.